Integrasion of Ethnoscience of Wayang Kulit in Guided Inquiry E-Modul to Strengthen Critical Thinking in Learning Light and Optical Devices - Manggul , F. Collin Maharani; Sholikhan; Pratiwi, Hestiningtyas Yuli (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2025)
The integration of ethnoscience into the guided inquiry-based e-module is driven by students’ low critical thinking skills caused by the dominance of conventional, teacher-centered learning methods. The physics topics of light and optical instruments are linked with elements of the traditional wayang kulit art as an ethnoscience approach to create more meaningful and contextual learning experiences. This study aims to develop an interactive and contextual e-module to enhance students’ critical thinking skills. The development model used is ADDIE, which consists of five stages: analysis, design, development, implementation, and evaluation. The research was conducted with 18 eighth-grade students at SMP Ma’arif 01 Nurul Muttaqin. Expert validation results showed that the e-module achieved feasibility scores of 84% for content and media, and 87% for language aspects. Teachers rated the practicality of the e-module very high with a score of 95%. During implementation, students’ critical thinking skills significantly improved, indicated by an average pretest score of 16.83 and a post-test score of 98.33. The N-Gain value of 0.9807 falls into the high category, demonstrating the e-module’s effectiveness in enhancing critical thinking abilities. Therefore, this guided inquiry-based ethnoscience e-module is both feasible and effective as an innovative and contextual science learning medium.